Frequency and Causative Factors of Splenic Trauma at Liaquat University Hospital/Jamshoro - Riaz Ahmed Shah, Suhail Ahmed Soomro, Abdul Sattar Abro, Muhammad Faheem Ahsan, Shahnawaz Khatti, Aneeta Kumari, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the frequency and causative factors of splenic trauma in patients presented with abdominal blunt trauma at the surgical emergency of the Liaquat University Hospital Jamshoro (Hyderabad). Material and methods: This was a cross-sectional and retrospective study, carried out at the surgical units of Liaquat University Hospital Jamshoro from December 2013 to November 2014. All the patients admitted with abdominal trauma, aged >12 years of either gender, were included. After taking informed consent, a complete medical history, especially regarding the cause of the injury, and a physical examination were done. All the patients were evaluated for splenic trauma after imaging diagnosis and operative findings. A self-made proforma was used for the data collection of age, gender, residence, causes of the injury, and presence of the splenic trauma. Data was analyzed by using SPSS version 26. Results: A total of 250 cases of abdominal trauma were studied, and splenic trauma cases were found in 60 (22.7%). Out of 60 participants, most of the cases were aged 18 to 30 years (46.7%) and 31 to 40 years (38.3%). Males were seen in the majority of 44 (73.3%), while females were 16 (26.7%). According to the causative factors of the splenic trauma, road traffic accidents were the most common (51.1%), followed by falls (19.1%), stab wounds (17.0%), and fire arm injuries (12.8%). Conclusion: As per the study conclusion, the young males mostly suffered from splenic trauma, which was observed to be 22.7% among patients with abdominal trauma. Road traffic accidents (RTA) and falls from height were observed to be the most common causative factors.